Association between income, employment status, and asthma outcomes: a systematic review and meta-analysisResearch in context - Zakariah Gassasse; Isaa D. Khan; Elliot Mok; Ayyash M. Asick; Andrew Tan; Aziz Sheikh; Ian Sinha; Gwyneth A. Davies; Hannah Whittaker; Constantinos Kallis; Jennifer K. Quint (The Lancet Regional Health. Europe)
Summary: Background: Health inequalities are deeply entrenched in society, and finding ways to reduce these, therefore, represents a major health policy challenge. Focusing on the two highest weighted Index of Multiple Deprivation domains, namely income and employment, we sought to synthesise the evidence on the association between these major determinants of socioeconomic status and asthma outcomes. Methods: In this systematic review and meta-analysis, we searched key concepts related to employment, income, and asthma outcomes using Medline and Embase for studies published between January 1, 2010 and April 3, 2025. Studies were eligible for inclusion if they were in English and described an association between income and/or employment and asthma outcomes, including exacerbations, hospital admissions and mortality, in people with asthma. Risk Of Bias In Non-randomized Studies–of Exposures (ROBINS-E), Risk of Bias (RoB) and adapted RoB tools were used to assess the risk of bias in the included studies. Using the restricted maximum likelihood method, we meta-analysed the rate of exacerbations and explored heterogeneity between age-related population groups: children (under 18 years) and adults (18 years and older). This study was registered with PROSPERO, CRD42024527300. Findings: We identified 4153 potentially eligible studies, of which 3141 were screened. 30 studies met the inclusion criteria, with most having a low risk of bias. 19 studies reported income as the exposure and exacerbation as the outcome, of which ten were included in the meta-analysis. People in the lowest income group were more likely to experience an asthma exacerbation than those in the highest income group: OR 1.25; 95% CI 1.13–1.37 overall and when stratified by age: children (1.36 [1.23–1.50]) and adults (1.19 [1.05–1.33]). Only three studies investigated the role of unemployment and were narratively synthesised. While unemployment was associated with increased emergency care visits, its role in predicting exacerbations was less clear. Interpretation: There is a need for upstream interventions aiming to reduce income inequalities and to investigate their impact on reducing asthma inequalities. Funding: Health Data Research UK, Inflammation and Immunity Driver Programme.